2008
DOI: 10.1128/cvi.00404-07
|View full text |Cite
|
Sign up to set email alerts
|

Memory T Cells Specific for Novel Human Papillomavirus Type 16 (HPV16) E6 Epitopes in Women Whose HPV16 Infection Has Become Undetectable

Abstract: Human papillomavirus (HPV)-specific T-cell response to the HPV type 16 (HPV16) E6 protein has been shown to be associated with successful viral clearance. The patterns of CD8 T-cell epitopes within HPV16 E6 protein were previously studied in two women with HPV16 clearance. The goal of this study was to characterize these epitopes in terms of their minimal and optimal amino acid sequences and the human leukocyte antigen (HLA) restriction molecules. The presence of the epitope-specific memory T cells after viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…In this fragment, the dominant epitope E6 29-37 is restricted by HLA-B48, E6 31-38 by HLA-B4002 and the subdominant epitope E6 52-61 by HLA-B35 (Nakagawa et al, 2007). The same group had also shown that the peptide E6 33-42 61 is recognized by CD8+ T lymphocytes in association with HLA-A68, peptide E6 52-61 in association with HLA-B57 and -B35, peptide E6 75-83 in association with HLA-B62, peptide E7 7-15 in association with HLA-B48 and peptide E7 79-87 in association with HLA-B60 (Nakagawa et al, 2004(Nakagawa et al, , 2007Wang et al, 2008). In addition, E7 7-15 is also able to bind HLA-A2 and -B8 to be recognized by CTL (Oerke et al, 2005;Ressing et al, 1995).…”
Section: How To Determine the Epitopic Regions For A Therapeutic Vaccmentioning
confidence: 87%
“…In this fragment, the dominant epitope E6 29-37 is restricted by HLA-B48, E6 31-38 by HLA-B4002 and the subdominant epitope E6 52-61 by HLA-B35 (Nakagawa et al, 2007). The same group had also shown that the peptide E6 33-42 61 is recognized by CD8+ T lymphocytes in association with HLA-A68, peptide E6 52-61 in association with HLA-B57 and -B35, peptide E6 75-83 in association with HLA-B62, peptide E7 7-15 in association with HLA-B48 and peptide E7 79-87 in association with HLA-B60 (Nakagawa et al, 2004(Nakagawa et al, , 2007Wang et al, 2008). In addition, E7 7-15 is also able to bind HLA-A2 and -B8 to be recognized by CTL (Oerke et al, 2005;Ressing et al, 1995).…”
Section: How To Determine the Epitopic Regions For A Therapeutic Vaccmentioning
confidence: 87%
“…A CD8 T-cell clone specific for the HPV-16 E6 aa-52-to-61 epitope restricted by the HLA class I B57 molecule has been shown to cross-recognize HPV-35 (␣9), -39 (␣7), -45 (␣7), -51 (␣5), and -73 (␣11) (35) (Table 4), while another CD8 T-cell clone specific for the same peptide but restricted by another HLA class I molecule, B58, has been shown to cross-recognize HPV-31 (␣9), -33 (␣9), -35 (␣9), -39 (␣7), -45 (␣7), -51 (␣5), -58 (␣9), and -73 (␣11) (36) ( Table 5). On the other hand, a CD8 T-cell clone recognizing the HPV-16 E6 aa-75-to-83 epitope restricted by the HLA class I B62 molecule (Table 6) and another clone recognizing the E6 aa-133-to-142 epitope restricted by the HLA class I A6801 molecule (Table 7) did not recognize any homologous peptides tested (37). Therefore, the presence of amino acid homology does not automatically lead to cross-recognition and it is not species specific when present.…”
Section: Cross-reactivitymentioning
confidence: 99%
“…Our group approached this question by isolating T-cell clones positive for an HPV-16 epitope and examining the recognition of homologous sequences from other high-risk HPV types using a gamma interferon (IFN-␥) enzyme-linked immunosorbent spot assay (ELISPOT) (35)(36)(37). If the number of spot-forming units for a homologous sequence from another HPV type was equal to or greater than 50% of the number for HPV-16, then that HPV type was considered to be cross-reactive.…”
Section: Cross-reactivitymentioning
confidence: 99%
“…During a natural infection, the growth of HPV-associated tumours is hindered and eradicated by E6-and E7-directed cytotoxic CTL responses (Coleman et al, 1994;Kadish et al, 2002;Wang et al, 2008). However preliminary studies using E6-and E7-targeting vaccines in humans has met with limited success (Borysiewicz et al, 1996;van Driel et al, 1999;Muderspach et al, 2000;Davidson et al, 2003;Frazer et al, 2004;Hallez et al, 2004;Kenter et al, 2008;Trimble et al, 2009) and there is currently no immunotherapeutic approach to treat HPV-associated carcinoma.…”
Section: Metastatic Lung Tumourmentioning
confidence: 99%
“…CTL responses targeting E7 and E6 are defined in mice (Feltkamp et al, 1993;Eiben et al, 2002;Peng et al, 2004) and are utilised for immunoprophylactic and immunotherapeutic anti-tumour strategies Greenstone et al, 1998;Chen et al, 1999;Chu et al, 2000;Schirmbeck et al, 2003a;Cassetti et al, 2004;Doan et al, 2005;Yan et al, 2007). CTL epitopes have also been defined in E6 and E7 in humans as potential targets for immunotherapeutic anti-tumour strategies (Kast et al, 1994;Peng et al, 2006b;Liu et al, 2007a;Nakagawa et al, 2007;Wang et al, 2008).…”
Section: Tc-1 Tumour Modelmentioning
confidence: 99%